(untitled) (Journal of actual problems of jurisprudence, 2018)
Agricultural production, as one of the most important sectors of the economy most exposed to weather conditions, natural disasters, as well as the impact of negative factors occurring in the economy (unequal exchange, price disparity, inflation, etc.). In this regard, agricultural producers in particular need of insurance protection. Especially because there is no clear legal framework, which is the need to develop and adopt a special regulation – Law on insurance of agricultural production. Key words: agriculture, insurance, agriculture, legal regulation.